Special education teachers job satisfaction in Malaysia: A review - Khairul Hanim Pazim; Roslinah Mahmud; Noor Fzlinda Fabeil; Juliana Langgat; Mohd Norazmi Nordin (Karadeniz Technical University, 2021)
Job satisfaction of special education teachers can be enjoyed when the teacher is able to focus on teaching MBK and the student shows the proper development. This job satisfaction if achieved will increase the commitment of teachers in performing their duties. However, if job satisfaction is not achieved, then avoidance and neglect of responsibilities will occur. This job satisfaction is important in producing the work productivity of special education teachers at the best level. This study was conducted to review previous studies related to job satisfaction of special education teachers. It is hoped that the findings of this study can help future researchers to get a clearer picture related to this issue.